The Future of Confession Law: Toward Rules for the Voluntariness Test - Primus, Eve Brensike (2015)
Confession law is in a state of collapse. Fifty years ago, three different doctrines imposed constitutional limits on the admissibility of confessions in criminal cases: Miranda doctrine under the Fifth Amendment, Massiah doctrine under the Sixth Amendment, and voluntariness doctrine under the Due Process Clauses of the Fifth and Fourteenth Amendments. But in recent years, the Supreme Court has gutted Miranda and Massiah, effectively leaving suspects with only voluntariness doctrine to protect them during police interrogations. The voluntariness test is a notoriously vague case-by-case standard. In this Article, I argue that if voluntariness is going to be the framework for confession law going forward, courts will need to disentangle the complex of values that is discussed under that heading and then use their clarified understanding as the basis for a judicially administrable rubric for regulating interrogation practices. As a matter of history and current practice, I argue that there are two different strands within voluntariness doctrine—one deontological strand that focuses on the offensiveness of the police methods used and one consequentialist strand that is concerned with the problem of false confessions. Courts could profit from disentangling those strands and creating different tests for each. Once the two strands are separated, voluntariness doctrine can move toward rules that are tailored to the distinctive values animating each strand. Toward that end, I propose different tests for determining the voluntariness of confessions going forward depending on which of the two strands is implicated in a given case